Buddhism : A very Short Introduction - Keown, Damien (Karachi, Pakistan Oxford University Press, 2000)
This "Very Short Introduction" introduces the reader both to the teachings of the Buddha and to the integration of Buddhism into daily life. It also provides a lively, challenging response to some of the most frequently asked questions about Buddhism.
Include Index, Colour Illustartion and Maps
Keywords: Buddhism -- Religion -- Boeddhisme